Autonomic SOA achieving fully "business-conscious" IT systems. - Mateos, Arthur (SOA webservices journal.)
Service-oriented architectures (SOA) and autonomic computing are among the hottest topics in IT today. SOA simplifies integration and facilitates the componentization of enterprise-wide systems, thereby enabling optimal business agility. Autonomic computing allows these systems to operate without human intervention-through self computing, self healing and self managing capabilities. By combining autonomic computing with SOA, enterprises can now achieve a new IT utopia, named "Autonomic SOA." However, this new level of autonomic computing goes beyond just reacting to traditional IT issues, such as increasing the speed to diagnose, repair, and prevent future issues. Autonomic SOA is also able to respond dynamically as changes occur within business conditions and processes, thereby empowering enterprises everywhere to achieve flawless execution on a daily basis.